2017
DOI: 10.3390/ijms18020316
|View full text |Cite
|
Sign up to set email alerts
|

Erythroid Differentiation Regulator 1 as a Novel Biomarker for Hair Loss Disorders

Abstract: Erythroid differentiation regulator 1 (Erdr1) is known to be involved in the inflammatory process via regulating the immune system in many cutaneous disorders, such as psoriasis and rosacea. However, the role of Erdr1 in various hair loss disorders remains unclear. The aim of this study was to investigate the putative role of Erdr1 in alopecias. Skin samples from 21 patients with hair loss disorders and five control subjects were retrieved, in order to assess their expression levels of Erdr1. Results revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Another important aspect is the EP itself. Piérard-Franchimont and Piérard [48] related the disrupted functionality of the EP with alopecia areata, [49,50]. The present study showed how CK15 and TE protein expression was modified in the EP of areas with AGA, suggesting that there is involvement of different components of scalp tissue with alopecia, with consequences for cellular homeostasis.…”
Section: Discussionsupporting
confidence: 54%
“…Another important aspect is the EP itself. Piérard-Franchimont and Piérard [48] related the disrupted functionality of the EP with alopecia areata, [49,50]. The present study showed how CK15 and TE protein expression was modified in the EP of areas with AGA, suggesting that there is involvement of different components of scalp tissue with alopecia, with consequences for cellular homeostasis.…”
Section: Discussionsupporting
confidence: 54%
“…The level of Erdr1 was significantly lower in severe type of the disease than in mild/moderate one, however, the level of IL-18 is significantly higher in severe form of AA than in mild/moderate form. In contrast, there is a study reported that the severity of AA was not significantly correlated with the intensity of Erdr1 expression 18 . Also, another study found nonsignificant differences in IL-18 levels between the patients with extensive and localized AA 8 .…”
Section: Discussionmentioning
confidence: 80%
“…Woo et al 18 proposed that down regulation of Erdr1 may be involved in the inflammatory cascade in AA and they explained the significant downregulation of Erdr1 expression in AA by these points: First, cellmediated immunity play the principal role in hair loss disorders 19 . Moreover, T helper 1 cytokines in AA are implicated in the dysregulation of the hair follicle's immune homeostasis 20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the sequence of human Erdr1 was not identified in the present study; the sequence of human Erdr1 will be analyzed in future studies. Our recent study reported that Erdr1 is a potential therapeutic agent for inflammatory skin diseases including psoriasis ( 25 ), rosacea ( 26 ) and hair loss disorders ( 39 ); therefore, we hypothesized in the present study that Erdr1 may also promote wound healing.…”
Section: Discussionmentioning
confidence: 95%